Pollen morphology of Rubiaceae from Cerrado forest fragments: Pollen unit, polarity and diversity of the types of apertures - Dutra, Fernanda Vitorete; Bellonzi, Talita Kely; Souza, Cintia Neves de; Gasparino, Eduardo Custódio [UNESP] (Elsevier, 2020)
The pollen morphology of 23 Brazilian native species of Rubiaceae Juss. from forest fragments of a Cerrado area was analyzed using light microscopy (LM) and scanning electron microscopy (SEM), in the search for new characters that might increase the knowledge on the pollen morphology of the species, and also aiming to help in the taxonomic characterization of the genera. For LM, the pollen grains were acetolyzed, measured, photographed and described qualitatively, whereas for SEM, the non-acetolyzed pollen grains were observed for further details of ornamentation. The analyzed species were grouped into three pollen types based on pollen unit and polarity, and three subtypes were separated considering the type of apertures; the surface ornamentation details were evidenced within each pollen type. The pollen grains are tetrad (Randia, microreticulate) or monad, apolar and inaperturate (Psychotria, reticulate-retipilate) or 2-porate (Coussarea, microreticulate), isopolar and porate (3-porate – Chomelia, reticulate-retipilate; Faramea, microreticulate-striate; Guettarda, reticulate-retipilate or rugulate; 3–4-porate – Tocoyena, foveolate; 6-porate – Mitracarpus, microreticulate-baculate), colpate (3-colpate – Psychotria, reticulate-retipilate; 7-colpate – Borreria, microreticulate-baculate), colporate (3-colporate – Chiococca and Ixora, microreticulate, Genipa and Simira, reticulate; Coutarea, microreticulate-echinate; Rudgea, microreticulate-baculate; 4-colporate – Manettia, reticulate). The metric data of the pollen grains examined by descriptive and multivariate analysis (Principal component analysis and Cluster analysis) allow the distinction of groups of species based on the size and shape. The results indicate the importance of qualitative and quantitative data and reinforce a wide morphological pollen diversity of Rubiaceae species from forest fragments in Cerrado which confirms the family as eurypalynous.
Keywords: Brazil; Eurypalynous; Palynology; Pollen types